Map of northernmost Labrador / American Geographical Society of New York - American Geographical Society of New York (1938)
Sheets 1-4 show relief by contours and spot heights; sheet 5 by hypsometric tints Sheets 1-4 at scale of 1:100,000 Most sheets include notes "Forbes: "Northernmost Labrador mapped from the air" Amer. Geogr. Soc. Special Publication No. 22" -- on each sheet Sheet No. 1 Cape Chidley. -- Sheet No. 2 Cape Kakkiviak. -- Sheet No. 3 Four Peaks. -- Sheet No. 4 Komaktorvik Fiord. -- Sheet No. 5 [Relief map] -- Sheet No. 6 Diagrammatic chart distribution of control in relation to areas covered by sheets 1-5 Color 1:100,000. 1:300,000